Effect of The Substitution of Compound Fertilizer With Single Fertilizer and Mycorrhizal Inoculation on The Growth and Yield of Soybean Among Eucalyptus - Apresus Sinaga; Didik Indradewa; Priyono Suryanto (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
The efforts to improve the productivity of soybean can be done through technological innovation by the provision of chemical fertilizers and mycorrhizae. This study were aimed to obtain information on the effect of a single fertilizer, which can provide the same or higher level of soybean crops if compared with those compound fertilizers, as well as to find out the effect of mycorrhizae to the improvement of efficiency in the use of inorganic fertilizers. It is expected that the mycorrhizae inoculation can reduce single fertilizer’s dose to the level equivalent to the compound fertilizer given by farmers. The study was conducted in Bleberan Village, Playen Subdistrict, Gunung Kidul Regency, Yogyakarta from February to May 2015. It was conducted by using a two-factors factorial design arranged in a randomized block design with three replications. The first factor was inorganic fertilizer (N, P2O5 and K2O), consisting of 5 levels, i.e. without fertilizer (0-0-0 kg/ ha), Phonska fertilizer (45-45-45 kg/ha), single fertilizer (45 -45-45 kg/ha), a low single fertilizer (23-36-30 kg/ha) and high single fertilizer (23-108-90 kg/ha). The second factor was mycorrhizal inoculation, consisting of three levels, i.e. without mycorrhizae (0 g), medium dose (2.5 g) and high dose (5 g). Data were analyzed using Analysis of Variance (ANOVA) at a significance level of 5%. If there was a significant difference, analysis was followed by Duncan Multiple Range Test with a significance level of 5%. The relationship between variables observed was examined by a correlation analysis. The results showed that there was no interaction between inorganic fertilizer and mycorrhizal application. The dose of single fertilizer which was equivalent to the dose of compound fertilizer given to soybean could increase crops by 1.37 t/ha compared with plants treated with a compound fertilizer 1.13 t/ha. The results of correlation analysis among parameters showed that there were correlations between the grain crops and height (r = 0.506**), stem diameter (r = 0.303*), and the number of pods per plant (r = 0.313*).